Policy of the Minister of Finance Related to Increasing the Annual Excise Price to Reduce Underage Smokers - Nanang Akbar Ayustin; Syofiati Lubis (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Indonesia has again received an unfavorable nickname from the international community. The number of adolescent smokers in Indonesia increases every year. They are generally produced by smokers’ parents/environment. This time, it is nicknamed the country of baby smokers because the highest number of smokers in Indonesia are teenagers and children. The National Commission for Child Protection (Komnas PA) Aris Merdeka Sirait when speaking in Advocacy for the Implementation of KTR Regional Regulations for journalists at the Santi Denpasar Hotel, Bali. According to Aris, up to now 69% of teenagers in Indonesia are active smokers. They live in a smoking environment and family. Besides that, There are 89 million children exposed to cigarette smoke and their health is at risk. Of these, there are 230 thousand children under the age of 10 who are already active smokers. Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 concerning Excise, defines Excise as a state levy imposed on certain goods which have the properties or characteristics specified in this law. Qualitative research methods make more effort in investigating the problem. These existing problems will be the basis used by researchers in retrieving data. Then the researcher determines the variables and measures them with numbers for analysis according to the procedures of the applicable statistics. Based on the results of this study, with the enactment of this Ministerial Regulation, the Head of Office re-stipulates excise rates with the following conditions: the re-set excise rates cannot be lower than the applicable excise rates, and/or n. The Retail Selling Price may not be lower than the applicable Retail Selling Price Limit per Stick or Gram, as stated in the Appendix which is an integral part of this Ministerial Regulation